2019
DOI: 10.1101/689802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of RNA condensation by the DEAD-box protein eIF4A

Abstract: eTOC Blurb: The RNA helicase eIF4A limits stress granule formation by reducing RNA condensation. Highlights:•! RNA condensates promote intermolecular RNA-RNA interactions at their surfaces! •! eIF4A helicase activity limits the recruitment of RNAs to stress granules in cells! •! eIF4A helicase activity reduces the nucleation of stress granules in cells! •! Recombinant eIF4A1 inhibits the condensation of RNA in vitro in an ATP-dependent manner! Keywords: DEAD-box protein, RNA-RNA interactions, stress granule, r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 79 publications
2
90
0
Order By: Relevance
“…Additionally, the features of the SARS-CoV-2 N protein that facilitate interaction with stress granules may also facilitate biomolecular condensation of N protein and genomic RNA during nascent virion formation at the ER-Golgi intermediate compartment (ERGIC) It is important to note that a recent study reported inhibition of SARS-CoV-2 replication in cell culture models treated with multiple translation inhibitors, including the eIF4A inhibitor zotatifin. 37 Inhibition of eIF4A is typically associated with increased stress granule formation 69,70 and can block replication of certain viruses. 71 However, the mechanism by which translation inhibitors suppress SARS-CoV-2 replication was not examined, so it is unclear whether stress granule induction or global suppression of translation (presumably including the production of SARS-CoV-2 proteins) is predominantly responsible for the observed antiviral effect.…”
Section: F I G U R Ementioning
confidence: 99%
“…Additionally, the features of the SARS-CoV-2 N protein that facilitate interaction with stress granules may also facilitate biomolecular condensation of N protein and genomic RNA during nascent virion formation at the ER-Golgi intermediate compartment (ERGIC) It is important to note that a recent study reported inhibition of SARS-CoV-2 replication in cell culture models treated with multiple translation inhibitors, including the eIF4A inhibitor zotatifin. 37 Inhibition of eIF4A is typically associated with increased stress granule formation 69,70 and can block replication of certain viruses. 71 However, the mechanism by which translation inhibitors suppress SARS-CoV-2 replication was not examined, so it is unclear whether stress granule induction or global suppression of translation (presumably including the production of SARS-CoV-2 proteins) is predominantly responsible for the observed antiviral effect.…”
Section: F I G U R Ementioning
confidence: 99%
“…Another class of proteins linked to cancer are confirmed regulators of SG assembly. For instance, members of RNA-dependent DEAD-box helicases (DDXs) are conserved regulators of RNA-containing condensates like SGs ( Hondele et al, 2019 ; Tauber et al, 2020 ). The ATPase activity of DDXs is required for controlling the partitioning of RNA between different types of condensates.…”
Section: Introductionmentioning
confidence: 99%
“…Another candidate as a general RNA chaperone is the ATP-dependent DEAD-box helicase eIF4A, which decreased RNA condensation in vitro and limited stress granule formation in live cells. [32] We conclude that pre-translational mRNPs appear to be single units absent from biomolecular condensates. A notable exception to this generalization is germ granules, in which stochastic seeding of single mRNPs is followed by multi-copy homotypic clustering in a sequenceindependent manner.…”
Section: Yesmentioning
confidence: 72%
“…This inference is based on analysis of mRNA in stress granules, exhibiting additional RNA-RNA interactions in the absence of ribosomes. [31,32] Pre-translational mRNPs containing EJC components, such as Magoh and eIF4A3, were found to behave like flexible rod-like structures or polymers. [6] The study by Metkar The low potential for higher-order mRNA structure is in line with earlier DMS and SHAPE probing studies in vivo.…”
Section: Remodeling Of Pre-translational Mrnps In the Cytoplasmmentioning
confidence: 99%